Lehr- und Schausammlungen im Wandel Archive, Displays, Objekte - Maget Dominicé, Antoinette; Stein, Claudius; Wolf, Niklas (Reimer Verlag, 2021)
How can public and university collections be preserved and exhibited in the future? Currently, the presentation of such collections is often determined by changes in the institutions. The history of disciplines and institutions plays a role, as does the focus of science on individual objects when it comes to provenance and exhibition possibilities. The authors address the challenges and future of teaching and display collections. In addition to the integration of objects in research and teaching, questions of the presentation of heterogeneous collections and uncertainties in the ownership of objects are addressed.